Hate the wait? How social inferences can cause customers who wait longer to buy more - Munichor, Nira; Cooke, Alan D. J. (Frontiers in Psychology, 2022)
Waiting is a mundane yet inevitable customer experience. Surprisingly, little research has analyzed the effects of waiting on subsequent customer behavior. The current research explores a counterintuitive effect of waiting times on behavior during a shopping trip: Longer waits, compared with shorter waits, can lead to a larger number of purchases despite generating more negative emotional reactions. Results of a field study and three lab experiments demonstrate this effect in the context of waiting for hedonic products. Consistent with a social-inference account, the experiments further show that the effect of waiting duration occurs when wait times are thought to depend on others’ preferences. This article explores the multifaceted effects of waiting duration on purchase behavior of hedonic products and sheds light on the social cognitions that underlie these effects.